Twenty-One Genres and How to Write Them - Dethier, Brock (Book collections on Project MUSE., 2013)
In this classroom-tested approach to writing, the author teaches readers how to analyze and write twenty-one genres that students are likely to encounter in college and beyond. This practical, task-oriented text confidently guides writers through step-by-step processes, reducing the anxiety commonly associated with writing tasks. This book presents each genre, provides a description of the genres' purpose, context, and discourse, and offers suggestions for writing activities or "moves" that writers can use to get words on the page